'Tension and release and tension and…': The Ethics of Narrative and Aesthetic Construction in Contemporary Streaming True Crime Docuseries. (March 2022) - Brookes, Daniel
Abstract : The critical and commercial success of the contemporary American long-form true crime docuseries has rapidly codified a series of narrative practices, particularly in works developed by streaming channels (Netflix, Amazon Prime) and premium cable networks (HBO) promoting quality television as part of their featured output. This article considers ethical concerns arising from the intersection of true crime documentary, narrative prorogation, and audio/visual rhetoric. Focusing primarily on Laura Ricciardi and Moira Demos' Making A Murderer (2015–2018), I argue that documentaries in this field develop – whilst also depoliticising and depersonalising – the narrative, aesthetic, and intellectual concepts introduced to the field by the so-called 'New Documentary'. I outline what is at stake in docuseries works intersecting the true crime genre which utilise aesthetic strategies of New Documentary that lack foundation in either the socially-minded counter-narrative or self-critique that has historically underscored their power: namely a narrative capability enriched by a medium demanding content in terms of the durational, but thwarted by the episodic 'bingeworthy' form that withholds information, the unyielding commercial demands of the platform, and the clashing of earnest fact-finding with a critical artifice shorn of its reason for deployment.